MONKEY KING - Sheih, Anita (Classic starts, 2024)
Sun Wukong is the "Monkey King"--and he has all the power and magic to prove it! But when his mischief lands him out of favor with the heavens, he must embark on a dangerous quest to deliver Buddhist scriptures. Will Monkey be able to control his impulsive behavior and complete his journey to the West?